ANALISIS EFEKTIFITAS PENGGUNAAN APLIKASI MOBILE JKN DALAM UPAYA PENINGKATKAN KUALITAS PELAYANAN DI TEMPAT PENERIMAAN PASIEN RSIA SITTI KHADIJAH 1 MUHAMMADIYAH MAKASSAR TAHUN 2024 - Syamsuddin, Syamsuddin -; Jayadie, Ahmad; Kamaruddin, Muh. Ihsan; Asmi, A Syamsinar (Politeknik Unggulan Kalimantan, 2025)
The JKN Mobile Application represents a significant advancement for BPJS Kesehatan as it simplifies the processes of registration and updating participant information, retrieving family member data, displaying participant contribution fees, and accessing services at primary healthcare facilities (FKTP) and advanced referral facilities (FKRTL). It also facilitates the submission of public complaints or suggestions. This study aims to determine the effectiveness of the JKN Mobile Application in improving service quality at the patient reception area of RSIA Sitti Khadijah 1 Muhammadiyah Makassar in 2024. This research employed a descriptive quantitative approach with a cross-sectional study design. Data collection was carried out using a questionnaire. The sampling technique used was purposive sampling, with a total of 152 patients as respondents. Based on the study, the chi-square test analysis yielded a p-value of 0.001 (p < 0.05), indicating that the JKN Mobile Application is effective in improving service quality at the designated patient reception area. The effectiveness is reflected in several aspects, including: Easy access and optimal service for JKN participants, User-friendly features and service functions, Simple procedures, Location-independent accessibility, Efficient access time, User-friendly interface design, Network stability, Ease in fulfilling JKN service needs, Assistance with administrative tasks, Benefits in obtaining JKN services.